The Influence Of Poverty And Unemployment On Economic Growth With Regional Income As Mediation Variables In East Java 2017-2021 - (UIN Maulana Malik Ibrahim), Sopiyatun (Mu'amalatuna: Jurnal Ekonomi Syariah, 2025)
Objective from study This For analyze the effect of poverty and unemployment on economic growth with regional income as a mediating variable in East Java 2017-2021 . In this study apply quantitative methods. The data used is the time series from 2017 to 2021 obtained from the Central Bureau of Statistics (BPS) for East Java Cities and Regencies. The secondary data is processed using path analysis techniques with the Smart PLS tool. Results this research show that Poverty has a positive effect on regional income in regencies and cities in East Java, poverty has a negative effect on economic growth in regencies and cities and cities in East Java, unemployment has a positive effect on regional income in regencies and cities in East Java, unemployment has a negative effect on economic growth in regencies and cities in East Java, Regional Income has no positive effect on Economic Growth in regencies and cities in East Java, Poverty has no indirect positive effect on Economic growth by mediating Regional Income in regencies and cities in East Java, Unemployment has no positive effect directly on Economic Growth through Regional Income in regencies and cities in East Java.